Porous carbon and method for producing same
By optimizing the pore structure and manufacturing methods of porous carbon, the problem of insufficient performance of existing porous carbon adsorbing large-diameter molecules or viruses is solved, and efficient adsorption of 2-200nm molecules or viruses is achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202380056030.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-27
- Filing Date
- 2023-07-20
- Publication Date
- 2025-03-14
AI Technical Summary
The existing porous carbon materials are not ideal in terms of adsorption properties of proteins or viruses, especially in a short period of time, and fail to effectively adsorb molecules or viruses with larger diameters.
By studying the structure and properties of porous carbon in detail, a specific manufacturing method is adopted, including using the LDF approximation method to determine the pressure change of nitrogen, and optimizing the pore structure, so that the slope of the mass transfer coefficient of porous carbon at a relative pressure of 1.0×10-4 and 1.0×10-3 is greater than 4, the pore diameter is greater than 2nm and less than 200nm, and the pore volume reaches more than 0.8cm3/g.
Porous carbon that exhibits excellent adsorption characteristics for molecules or viruses with larger diameters (for example, 2-200 nm), is realized, and is suitable for the fields of medicine, food refining and waste liquid treatment.
Smart Images

Figure CN119630606A_ABST
Abstract
Description
Technical Field
[0001] This patent application claims Paris Convention priority based on Japanese Patent Application No. 2022-119926 (filing date: July 27, 2022), the entirety of which is incorporated herein by reference.
[0002] The present invention relates to porous carbon and a method for producing the same. Background Art
[0003] As an adsorption material for proteins or viruses, activated carbon or porous carbon is tried.
[0004] For example, Patent Document 1 discloses that a porous carbon material made of a plant-derived material can adsorb proteins such as albumin. Patent Document 2 discloses that a porous carbon material made of a plant-derived material can adsorb and remove viruses. Patent Document 3 discloses that activated carbon adsorbs proteins such as albumin.
[0005] In addition, Patent Document 4 discloses an adsorption / desorption agent comprising porous carbon, characterized in that it comprises porous carbon, wherein the porous carbon has micropores and mesopores and / or macropores, and presents the following structure: the outer contours of the three types of pores are composed of carbonaceous walls, and the micropores are formed in a manner connected to the mesopores and / or macropores, and the adsorption / desorption agent uses nitrogen as an adsorption gas, and the relative pressure (P / P) when measured at 77K is 0 ) is set as x, and the mass transfer coefficient (K sap ) is set to y, x is 1.0×10 -5 ≤x≤1.0×10 -4 The relationship between x and y satisfies the formula: y ≥ 1.67 × 10 -1 x+2.33×10 -6 .
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-042569
[0009] Patent Document 2: Japanese Patent Application Publication No. 2012-187571
[0010] Patent Document 3: Japanese Patent Application Publication No. 2018-001057
[0011] Patent Document 4: International Publication No. 2014 / 142187
[0012] Patent Document 5: Japanese Patent Application Publication No. 2016-041656 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, according to the studies conducted by the present inventors, the porous carbon materials and activated carbons described in Patent Documents 1 to 3 may not have sufficient performance in terms of adsorption performance of proteins, viruses, etc., especially in terms of adsorption performance in a short period of time.
[0015] In addition, regarding the adsorption / desorption agent comprising porous carbon described in Patent Document 4, it is described that, compared with the adsorption / desorption agent comprising zeolite or activated carbon as a comparative material, at a relative pressure of 1.0×10 -5 ≤x≤1.0×10 -4 The value of the mass transfer coefficient within the range of is large, thereby enabling smooth adsorption of gas or liquid. Patent Document 5 discloses porous carbon having mesopores, micropores, and carbonaceous walls constituting the outer contours of the mesopores, wherein the carbonaceous walls present a three-dimensional network structure, and states that: when the porous carbon is used as a gas adsorbent, the flow of gas is not hindered, and therefore, the gas adsorption capacity is improved. However, Patent Documents 4 and 5 do not disclose the adsorption performance of molecules or viruses having a larger diameter.
[0016] An object of the present invention is to provide porous carbon that exhibits excellent adsorption characteristics for molecules or viruses having a relatively large diameter (for example, 2 to 200 nm).
[0017] Means used to solve problems
[0018] The present inventors have conducted detailed studies on porous carbon to solve the above problems and have completed the present invention. That is, the present invention includes the following preferred embodiments.
[0019] [1] Porous carbon, wherein the pressure change of nitrogen gas until adsorption equilibrium is reached at each predetermined relative pressure in the measurement of nitrogen adsorption isotherm is converted into a mass transfer coefficient by using LDF approximation, and the relative pressure is 1.0×10 -4 Above and 1.0×10 -3 The slope of the approximate straight line obtained by linearly approximating the relationship between the relative pressure and the mass transfer coefficient when the pressure is less than 200 nm is 4 or more, and the pore volume of the pores with a diameter of 2 nm or more and 200 nm or less calculated by the BJH method based on the nitrogen adsorption isotherm is 0.8 cm 3 / g or above.
[0020] [2] The porous carbon according to [1], wherein the relative pressure in the approximate straight line is 1.0×10 -3 The mass transfer coefficient is 3.0×10 -3 above.
[0021] [3] The porous carbon according to [1] or [2], wherein the volume density is less than 0.10 g / cm 3 .
[0022] [4] A method for producing porous carbon according to any one of [1] to [3], comprising: (1) a step of obtaining a mixture comprising a carbon source and a calcium compound; (2) a step of heat-treating the mixture in an inert gas atmosphere to phase separate the carbon source and the calcium compound; (3) a step of heat-treating the phase-separated mixture in an inert gas atmosphere to obtain a carbide; and (4) a step of removing the calcium compound from the carbide.
[0023] [5] The method according to [4] above, wherein the temperature in the phase separation step of step (2) is 150°C or higher and 500°C or lower.
[0024] [6] The porous carbon according to any one of [1] to [3] above, which is an adsorbent.
[0025] [7] The porous carbon according to any one of [1] to [3] and [6], which is an adsorbent material for adsorbing proteins.
[0026] [8] The porous carbon according to any one of [1] to [3] and [6], which is an adsorbent material for adsorbing viruses.
[0027] Effects of the Invention
[0028] According to the present invention, a porous carbon having excellent adsorption properties for molecules or viruses having a relatively large diameter (e.g., 2 to 200 nm) can be provided. Thus, by using the porous carbon of the present invention as, for example, a refining material for manufacturing medicines or foods, or as a material for removing macromolecules or viruses from waste liquids (wastewater), or as a material for antiviral sprays or antiviral masks, excellent properties can be obtained. Here, the molecular diameter refers to the average molecular diameter, and the virus diameter refers to the average diameter of the virus. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a graph showing the relationship between the relative pressure and the mass transfer coefficient related to the porous carbon of Example 2. DETAILED DESCRIPTION
[0030] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the following is an explanation of embodiments of the present invention, and does not mean that the present invention is limited to the following embodiments.
[0031] [Porous Carbon]
[0032] In the measurement of the nitrogen adsorption isotherm of the porous carbon of the present invention, the LDF (Linear Driving Force) approximation is used to set the relative pressure (P / P 0 ) is converted into the mass transfer coefficient for the nitrogen gas pressure change until the adsorption equilibrium is reached at a relative pressure of 1.0×10 -4 Above and 1.0×10 -3 The relationship between the relative pressure and the mass transfer coefficient at the following time is linearly approximated, and the slope of the approximate straight line obtained thereby is greater than 4. Here, P is the adsorption equilibrium pressure, P 0 The saturated vapor pressure is 0.8 cm. 3 / g or above.
[0033] These two technical features represent the characteristic pore structure of porous carbon, and thus the porous carbon of the present invention can exhibit desired adsorption characteristics.
[0034] <Relationship between mass transfer coefficient and relative pressure and value of mass transfer coefficient>
[0035] The mass transfer coefficient of porous carbon is an indicator of the movement speed of the adsorbate when it moves in the porous carbon. The greater the change in the mass transfer coefficient relative to the change in relative pressure, the easier it is for the adsorbate to move smoothly from the pores where macromolecules or viruses diffuse to the smaller pores where macromolecules or viruses are adsorbed, and the easier it is for the adsorbate to move smoothly from the pores where macromolecules or viruses are adsorbed to the larger pores where macromolecules or viruses diffuse. In addition, the larger the mass transfer coefficient, the faster the movement speed of the adsorbate in the pores of the porous carbon. Therefore, by investigating the change in the mass transfer coefficient and the value of the mass transfer coefficient associated with the change in relative pressure, the adsorption characteristics of porous carbon can be evaluated.
[0036] The relationship between relative pressure and mass transfer coefficient and the value of mass transfer coefficient can be investigated by preparing an adsorption isotherm by adsorbing nitrogen to porous carbon at -196°C and analyzing the adsorption isotherm. Specifically, as described in the examples described later, a nitrogen adsorption isotherm of porous carbon is prepared, and the pressure change of nitrogen until adsorption equilibrium is reached at each specified relative pressure is converted into a mass transfer coefficient using the LDF approximation. Next, by preparing a graph with relative pressure as the x-axis and mass transfer coefficient as the y-axis, the relationship between relative pressure and mass transfer coefficient can be expressed.
[0037] The inventors found that: in this figure, if the relative pressure is 1.0×10 -4 Above and 1.0×10 -3When the slope of the approximate straight line drawn within the following range [this slope may be referred to as (a) in this specification] is 4 or more, the porous carbon can exhibit desired adsorption characteristics (such as high adsorption amount and high adsorption rate, especially high adsorption rate).
[0038] Here, the relative pressure range is set to 1.0×10 -4 Above and 1.0×10 -3 The reason is as follows. In this specification, molecules with a relatively large diameter (e.g., 2 to 200 nm) (e.g., proteins such as albumin and antibodies) or viruses are assumed as adsorbents. It can be considered that if the relative pressure is too small, that is, the relative pressure is less than 1.0×10 -4 When the relative pressure is too high, that is, when the relative pressure is greater than 1.0×10 -3 , the adsorption behavior in pores larger than the pores that effectively function as adsorption sites for the adsorbate is reflected in the mass transfer coefficient. -4 Above and 1.0×10 -3 Hereinafter, the region in which the adsorption behavior of the adsorbate assumed in the present specification is reflected in the mass transfer coefficient can be evaluated, and the slope of the approximate straight line in this range can be used as one of the indicators of the adsorption performance of the adsorbate.
[0039] For a more specific calculation method for (a), use Figure 1 The relationship between the relative pressure and the mass transfer coefficient of the porous carbon in Example 2 described later will be described below.
[0040] First, in the graph showing the relationship between relative pressure and mass transfer coefficient prepared as described in the examples below, the relative pressure is 1.0×10 -4 Above and 1.0×10 -3 The following range (in Figure 1 Draw an approximate straight line within the range (indicated by a dotted line and arrow in FIG. 1 ). Next, find the slope (a) of the approximate straight line.
[0041] When (a) is less than 4, the porous carbon is difficult to show the desired adsorption characteristics. (a) is 4 or more, preferably 5.5 or more, more preferably 6 or more (for example, 6.5 or more), further preferably 7 or more (for example, 7.5 or more), and particularly preferably 8 or more (for example, 8.15 or more). If (a) is greater than the above lower limit, there is a tendency that the porous carbon has a pore structure suitable for adsorbing the adsorbate, and therefore, it is easy to show the desired adsorption characteristics. In addition, (a) is usually 10 or less.
[0042] The relative pressure of the approximate straight line in the above range is 1.0×10 -3 The value of the mass transfer coefficient when (this value is sometimes referred to as (b) in this specification) is preferably 3.0×10 -3 More preferably, 5.0×10 - 3 More preferably, 6.0×10 -3 Above (e.g. 7.0×10 -3 More than 8.0×10 -3 If (b) is equal to or greater than the above lower limit, the porous carbon tends to have a pore structure suitable for adsorbing the adsorbate, and thus, the desired adsorption characteristics are likely to be exhibited. -2 If you use Figure 1 The diagram shown in Figure 1 shows that (b) is a relative pressure of 1.0×10 -3 (the right end of the dotted line or the arrow) is the value of the mass transfer coefficient.
[0043] It can be considered that the above-mentioned "pore structure suitable for adsorption of adsorbate" means that there are many pores that effectively act as adsorption sites for adsorbate, the openings of such pores have a size suitable for the entry and exit of adsorbate, the proportion of pores connected from the opening at one end to the opening at the other end (pores with an opening at one end and no blockage at the other end) is high, there are few structures (such as bottlenecks, etc.) that hinder the movement of adsorbate in the connected parts, and the pore structure has a short path for the adsorbate to move in the porous carbon (for adsorption or desorption). Therefore, the pore structure of the porous carbon of the present invention is distinguished from a "three-dimensional network structure" formed by mixing and carbonizing a carbon source with mold particles (pore source) and removing the already aggregated / connected mold particles (continuous pores generated by removing existing mold particles) and the surrounding carbon skeleton, in which the path along which the adsorbate moves (for adsorption or desorption) is long, and there are multiple pore structures (such as bottlenecks, etc.) that hinder the movement of the adsorbate corresponding to the areas between the existing mold particles or the gaps between continuously existing mold particles.
[0044] In a preferred embodiment of the present invention, it is considered that all the pores are connected from the opening at one end to the opening at the other end.
[0045] In addition, it can be considered that (a) corresponds to the length of the path through which the adsorbate moves in the porous carbon (for adsorption or desorption), and it can be considered that the larger (a) is, the shorter the length of the path is. It can be considered that (b) corresponds to the amount of structure that hinders the movement of the adsorbate in the connecting part, and it can be considered that the larger (b) is, the less the structure that hinders the movement of the adsorbate is.
[0046] (a) A porous carbon having a value above the aforementioned lower limit can be manufactured as follows: for example, a carbon source and a pore source are mixed in a highly compatible state, the resulting mixture is phase-separated by heat treatment, and then the phase-separated structure is fixed by carbonization, and the pore source is removed from the resulting carbide, thereby manufacturing. For example, in the method for manufacturing porous carbon described later, (a) can be adjusted to above the aforementioned lower limit by appropriately adjusting the temperature and time of heat-treating a mixture of a carbon source and a calcium compound that serves as a pore source, or by changing the type of carbon source and appropriately adjusting the temperature and time of heat-treating the aforementioned mixture. In addition, (b) can also be adjusted to above the aforementioned lower limit by appropriately adjusting the same conditions.
[0047] <Pore volume with a pore diameter of 2 nm or more and 200 nm or less>
[0048] In the porous carbon of the present invention, the pore volume with a pore diameter of 2 nm or more and 200 nm or less (hereinafter sometimes referred to as "pore volume of 2 nm or more and 200 nm or less") calculated by the BJH method based on the nitrogen adsorption isotherm is 0.8 cm 3 / g or more. It can be considered that the pores between 2nm and 200nm significantly interfere with the adsorption and desorption of the adsorbate. Therefore, if the volume of the pores between 2nm and 200nm is less than 0.8cm 3 / g, it is difficult for the porous carbon to have the desired adsorption characteristics.
[0049] The volume of pores with a diameter of 2 nm or more and 200 nm or less is preferably 0.90 cm 3 / g or more, more preferably 1.00cm 3 / g or more, more preferably 1.30cm 3 / g or more, and more preferably 1.60cm 3 / g or more, particularly preferably 1.90cm 3 / g or more, more preferably 2.00cm 3 / g or more, and particularly preferably 2.20cm 3 When the pore volume of 2 nm to 200 nm is greater than the above lower limit, the porous carbon is likely to have the desired adsorption characteristics. The upper limit of the pore volume of 2 nm to 200 nm is not particularly limited, but is usually 4.00 cm 3 / g or less, preferably 3.90cm 3 / g or less.
[0050] The pore volume of 2 nm or more and 200 nm or less can be adjusted to above the aforementioned lower limit and below the aforementioned upper limit by, for example, appropriately adjusting the type and / or ratio of the carbon source and the calcium compound in the method for manufacturing porous carbon described later; the temperature and / or time of the heat treatment process (phase separation process and / or carbonization process), etc. The pore volume of 2 nm or more and 200 nm or less can be calculated by analyzing the nitrogen adsorption isotherm of porous carbon using the BJH method, and can be obtained by, for example, the method described in the examples described later.
[0051] <Mode diameter>
[0052] In porous carbon, the mode diameter of pores calculated by the nitrogen adsorption isotherm and the BJH method (hereinafter sometimes referred to as the "mode diameter") can be, for example, less than 200 nm, less than 190 nm, or less than 180 nm, for example, more than 2 nm, more than 10 nm, or more than 20 nm. Here, the "mode diameter" refers to the pore diameter with the largest ratio in the logarithmic differential pore volume distribution [dV / d(logD)] obtained by differentiating the cumulative pore volume (V) using the common logarithm of the pore diameter (D). There is a tendency that the smaller the mode diameter of porous carbon, the more preferred the adsorption characteristics of small-sized molecules, viruses, and bacteria, and there is a tendency that the larger the mode diameter of porous carbon, the better the adsorption characteristics of large-sized molecules, viruses, and bacteria. Therefore, by adjusting the mode diameter of porous carbon according to the size of molecules, viruses, and bacteria, porous carbon is easy to have the desired adsorption characteristics.
[0053] The mode diameter can be adjusted to above the aforementioned lower limit and below the aforementioned upper limit by, for example, appropriately adjusting the type and / or ratio of the carbon source and the calcium compound in the method for producing porous carbon described later; the temperature and / or time of the heat treatment process (phase separation process and / or carbonization process), etc. The mode diameter can be calculated by analyzing the nitrogen adsorption isotherm of porous carbon using the BJH method, and can be obtained by, for example, the method described in the examples described later.
[0054] <Volume Density>
[0055] The volume density of porous carbon indicates the degree of development of the pore structure. When the pore volume with a pore diameter of 2 nm or more and 200 nm or less is the same, the volume density is low and the volume of the pore with a pore diameter exceeding 200 nm becomes larger. It can be considered that: the pores with a pore diameter of 2 nm or more and 200 nm or less are responsible for the movement and adsorption of macromolecules or viruses, and on the other hand, the pores with a pore diameter exceeding 200 nm are responsible for the entrance or movement path for macromolecules or viruses to move smoothly to the pores with a pore diameter of 2 nm or more and 200 nm or less. Therefore, it is preferred that: on the basis of the pore volume with a pore diameter of 2 nm or more and 200 nm or less, the pore volume with a pore diameter of 200 nm or more is large, that is, the volume density is small.
[0056] In a preferred embodiment, the volume density of the porous carbon is preferably less than 0.10 g / cm 3 , more preferably 0.08 g / cm 3 Below, more preferably 0.06 g / cm 3 Below, particularly preferably 0.03 g / cm 3 If the volume density is less than the above upper limit or is below the above upper limit, macromolecules or viruses can smoothly move into the pores with a pore diameter of 2 nm or more and 200 nm or less, and as a result, the desired adsorption characteristics are easily exhibited. The lower limit of the volume density of porous carbon is not particularly limited, but is usually 0.001 g / cm 3 More than, preferably 0.005 g / cm 3 When the bulk density is equal to or higher than the above lower limit, scattering is easily suppressed when the porous carbon is used as an adsorbent, and the handling property is easily improved.
[0057] The volume density can be adjusted to above the aforementioned lower limit value and less than the aforementioned upper limit value or below the aforementioned upper limit value by, for example, appropriately adjusting the temperature and time when heat treating the mixture of the carbon source and the calcium compound in the later-described method for producing porous carbon, or by changing the type of carbon source and appropriately adjusting the temperature and time when heat treating the aforementioned mixture.
[0058] The bulk density can be measured by, for example, the method described in Examples below.
[0059] <Pore volume with pore diameter less than 2 nm>
[0060] In a preferred embodiment, the pore volume of pores with a diameter of less than 2 nm calculated by the DFT method based on the nitrogen adsorption isotherm of the porous carbon is preferably 0.35 cm 3 / g or less, more preferably 0.32cm 3 / g or less, more preferably 0.30cm 3 / g or less, particularly preferably 0.28cm 3 / g or less, and more preferably 0.25cm 3 / g or less, more preferably 0.23cm 3 / g or less, and more preferably 0.21cm 3 / g or less, and particularly preferably 0.20cm 3 / g or less. Pores with a pore diameter of less than 2 nm are pores that cannot adsorb macromolecules or viruses with a diameter of 2 to 200 nm. If the volume of pores with a pore diameter of less than 2 nm is below the aforementioned upper limit, there is a tendency for the volume of pores with a pore diameter of 2 to 200 nm to be high, and therefore, it is easy to exhibit the desired adsorption characteristics. The lower limit of the volume of pores with a pore diameter of less than 2 nm is not particularly limited, but is preferably 0.01 cm 3 / g or more. The pore volume with a pore diameter less than 2nm can be adjusted to above the aforementioned lower limit and below the aforementioned upper limit by, for example, appropriately adjusting the type and / or ratio of the carbon source and the calcium compound in the method for manufacturing porous carbon described later; the temperature and / or time of the heat treatment process (phase separation process and / or carbonization process), etc. The pore volume with a pore diameter less than 2nm can be obtained by analyzing the adsorption isotherm obtained by nitrogen adsorption measurement of porous carbon using the QS-DFT method, and calculating the volume of pores with a pore diameter less than 2nm.
[0061] <Specific surface area calculated by BET method>
[0062] In a preferred embodiment, the specific surface area calculated by the BET method based on the nitrogen adsorption isotherm of the porous carbon is preferably 300 m 2 / g or more, more preferably 400m 2 / g or more, more preferably 450m 2 / g or more, particularly preferably 500m 2 / g or more, and preferably 1200m 2 / g or less, more preferably 1100m 2 / g or less, more preferably 1000m 2 / g or less. If the specific surface area is above the aforementioned lower limit and below the aforementioned upper limit, there is a tendency for the porous carbon to have a plurality of pores with a pore diameter of 2 to 200 nm suitable for adsorbing macromolecules or viruses, and therefore, it is easy to exhibit the desired adsorption characteristics. The specific surface area can be adjusted to above the aforementioned lower limit and below the aforementioned upper limit by, for example, appropriately adjusting the type and / or proportion of the carbon source and the calcium compound in the method for producing the porous carbon described later; the temperature and / or time of the heat treatment process (phase separation process and / or carbonization process), etc. The specific surface area can be calculated by measuring the adsorption isotherm of the porous carbon, and analyzing the adsorption isotherm based on the multi-point method using the BET formula, and using the obtained curve as an approximate straight line in the range of relative pressure of 0.05 or more and 0.1 or less.
[0063] <Calcium content>
[0064] In a preferred embodiment, the calcium content in the porous carbon is preferably more than 20 ppm, more preferably more than 50 ppm, further preferably more than 100 ppm, and preferably less than 2000 ppm, more preferably less than 1500 ppm, and further preferably less than 1000 ppm. If the calcium content is above the aforementioned lower limit and below the aforementioned upper limit, there is a tendency to easily suppress excessive increase in the mass of the porous carbon and excellent productivity. The calcium content can be adjusted to above the aforementioned lower limit and below the aforementioned upper limit by, for example, appropriately adjusting the conditions of the process for removing the calcium compound in the manufacturing method of the porous carbon described later (e.g., the type and / or concentration of the acid used in the acid cleaning, the time and / or temperature of the acid cleaning, etc.).
[0065] <Sulfur content and silicon content>
[0066] In a preferred embodiment, the sulfur content in the porous carbon is preferably less than 1000 ppm, more preferably less than 900 ppm, and further preferably less than 800 ppm. In addition, in a preferred embodiment, the silicon content in the porous carbon is preferably less than 1000 ppm, more preferably less than 900 ppm, and further preferably less than 800 ppm. If the content of sulfur and silicon is below the aforementioned upper limit, there is a tendency to easily suppress excessive increase in the mass of the porous carbon and excellent productivity. The lower limit of the content of sulfur and silicon is not particularly limited and can be 0 ppm. The content of sulfur and silicon can be adjusted to below the aforementioned upper limit by, for example, appropriately selecting the type of carbon source in the method for manufacturing porous carbon described later; and / or appropriately adjusting the conditions of the process for removing calcium compounds (such as the type and / or concentration of the acid used in the acid cleaning, the time and / or temperature of the acid cleaning, etc.).
[0067] The contents of calcium, sulfur and silicon can be determined by fluorescent X-ray analysis.
[0068] <Average primary particle size>
[0069] In a preferred embodiment, the porous carbon is preferably in a granular form.
[0070] In this embodiment, the average primary particle size of the porous carbon is preferably 1 μm or more, more preferably 2 μm or more, particularly preferably 5 μm or more, and preferably 80 μm or less, more preferably 60 μm or less. If the average primary particle size is above the lower limit and below the upper limit, there is a tendency for excellent adsorption performance.
[0071] The average primary particle size can be adjusted to above the aforementioned lower limit and below the aforementioned upper limit by, for example, appropriately selecting the type of carbon source in the method for producing porous carbon described later; and / or appropriately adjusting the conditions of the pulverization process, etc. In this specification, the average primary particle size refers to the particle size at which the cumulative volume measured by the laser diffraction / scattering method becomes 50%. In the case where the laser diffraction / scattering method cannot be used for measurement, the average primary particle size sometimes refers to: the average particle size obtained by measuring the particle size of the primary particles shown in the electron microscope image and calculating the average value.
[0072] [Method for producing porous carbon]
[0073] The porous carbon of the present invention can be produced by, for example, a method comprising the following steps:
[0074] (1) A step of obtaining a mixture containing a carbon source and a calcium compound;
[0075] (2) a step of heat-treating the mixture in an inert gas atmosphere to phase separate the carbon source and the calcium compound;
[0076] (3) a step of heat treating the phase-separated mixture in an inert gas atmosphere to obtain a carbide; and
[0077] (4) A step of removing calcium compounds from the carbide.
[0078] <Step (1)>
[0079] The carbon source is not particularly limited. From the viewpoint of improving compatibility with the calcium compound that serves as the pore source, the carbon source is preferably a carbohydrate. Examples of carbohydrates include monosaccharides such as glucose, galactose, mannose, fructose, ribose, and glucosamine; disaccharides such as sucrose, trehalose, maltose, cellobiose, maltitol, lactobionic acid, and lactosamine; and polysaccharides such as starch, cellulose, glycogen, pectin, curdlan, and guar gum. These carbohydrates can be used alone or in combination of two or more. Among these carbohydrates, glucose and starch are preferred from the viewpoint of being easy to manufacture porous carbon that exhibits the desired adsorption characteristics and being easy to obtain in large quantities.
[0080] As starch, there is no particular limitation, and for example, starch derived from corn, cassava, potato, sweet potato, tapioca, bean, wheat, rice, etc. can be used. The preferred amylose content of starch is preferably 50% by mass or less, more preferably 30% by mass or less relative to the mass of starch. There is a tendency that the lower the amylose content of starch, the lower the gelatinization temperature. Therefore, if the amylose content of starch is below the aforementioned upper limit, it is easy to gelatinize at low temperatures, and the compatibility with the calcium compound that becomes the source of pores is easily improved, so it is preferred. The above-mentioned amylose content can be obtained by, for example, iodine colorimetry. In addition, the starch can be a modified starch that has been modified. As modified starch, for example, etherified starch, esterified starch, cationized starch, and cross-linked starch can be listed. Starch can be used alone or in combination of two or more. When two or more are used in combination, the above-mentioned amylose content is the average amylose content of the combined starch.
[0081] The pore source is not particularly limited. From the viewpoint of easily improving the compatibility with the carbon source, the pore source is preferably a calcium compound. As the calcium compound, it is not particularly limited, and for example, calcium chloride, calcium hydroxide, calcium oxide, calcium carbonate, calcium acetate, calcium fluoride, calcium bromide, calcium iodide, calcium carbide, calcium bicarbonate, calcium nitrate, calcium sulfate, calcium silicate, calcium phosphate, calcium pyrophosphate, calcium gluconate, calcium lactate, etc. can be used. Among these calcium compounds, from the viewpoint of easily manufacturing porous carbon exhibiting the desired adsorption characteristics, it is preferred that the melting point is 300°C or less (in the case where the mixture contains water and / or polyols and / or carboxylic acids described later, the melting point of the eutectic compound of the calcium compound and the carbon source and water and / or polyols and / or carboxylic acids is 300°C or less), and more preferably at least one selected from calcium chloride hydrate, calcium hydroxide, calcium oxide, calcium carbonate and calcium acetate. There are dihydrates, tetrahydrates and hexahydrates in calcium chloride hydrates, and any hydrate can be used. From the aspect of good reactivity with sugars, dihydrates are preferred.
[0082] The mixture containing the carbon source and the calcium compound may further contain at least one selected from water, a polyol and a carboxylic acid. It can be considered that if the mixture contains water and / or a polyol and / or a carboxylic acid, the carbon source and the calcium compound are compatible with each other with the help of water and / or a polyol and / or a carboxylic acid to form a eutectic compound. Therefore, the melting point of the calcium compound having a melting point of more than 300°C alone can be made below 300°C in terms of the melting point of the eutectic compound. Therefore, in this specification, "the melting point of the calcium compound is below 300°C" also includes "the melting point of the eutectic compound of water and / or a polyol and / or a carboxylic acid, a carbon source and a calcium compound is below 300°C". From the viewpoint of easy acquisition, water is preferred. As usable polyols, for example, glycerol, ethylene glycol, propylene glycol, polyethylene glycol and polypropylene glycol can be listed. Among these polyols, glycerol and ethylene glycol are preferred from the viewpoint of easy dissolution of calcium compounds and easy acquisition in large quantities. As usable carboxylic acid, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, lactic acid, malic acid, citric acid, benzoic acid, phthalic acid, salicylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid and maleic acid etc. can be listed. Among these carboxylic acids, from the viewpoint of easily dissolving calcium compound, easily obtaining in a large amount, formic acid and acetic acid are preferably used. When two or more of water, one or more polyols and one or more carboxylic acids are mixed and used, the use ratio of two or more of water, polyols and carboxylic acids can be appropriately changed according to the desired properties of porous carbon.
[0083] The method of mixing the carbon source and the calcium compound, and optionally water, a polyol, and / or a carboxylic acid is not particularly limited, and the carbon source and the calcium compound may be mixed by any mixing method.
[0084] The amount of the calcium compound mixed with the carbon source is preferably 80 parts by mass or more, more preferably 130 parts by mass or more, and further preferably 180 parts by mass or more, and preferably 500 parts by mass or less, more preferably 400 parts by mass or less, and further preferably 300 parts by mass or less, relative to 100 parts by mass of the carbon source. If the amount of the calcium compound is above the lower limit and below the upper limit, the relationship between the mass transfer coefficient and the relative pressure of the obtained porous carbon and the pore volume are likely to become appropriate.
[0085] When the mixture containing a carbon source and a calcium compound further contains water and / or a polyol and / or a carboxylic acid, the amount of water and / or a polyol and / or a carboxylic acid (the total amount when two or more of water, one or more polyols and one or more carboxylic acids are used) is preferably 50 parts by mass or more, more preferably 100 parts by mass or more, and further preferably 150 parts by mass or more, relative to 100 parts by mass of the carbon source, and is preferably 500 parts by mass or less, more preferably 400 parts by mass or less, and further preferably 300 parts by mass or less. Among them, when the mixture containing a carbon source and a calcium compound does not contain a polyol and a carboxylic acid but contains water, the amount of water is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and further preferably 50 parts by mass or more, relative to 100 parts by mass of the carbon source, and is preferably 500 parts by mass or less, more preferably 400 parts by mass or less, and further preferably 300 parts by mass or less. When the amount of water and / or polyol and / or carboxylic acid is not less than the aforementioned lower limit and not more than the aforementioned upper limit, a eutectic compound is likely to be produced, and therefore the relationship between the mass transfer coefficient and the relative pressure and the pore volume of the obtained porous carbon are likely to become appropriate.
[0086] <Step (2)>
[0087] In the step (2), the mixture obtained in the step (1) is heat-treated in an inert gas atmosphere to phase-separate the carbon source and the calcium compound.
[0088] As the inert gas, for example, nitrogen, argon and mixtures thereof can be cited. The lower the concentration of the oxidizing gas in the gas used, the more preferably. The concentration of the oxidizing gas, especially oxygen, is usually 1% by volume or less, more preferably 0.1% by volume or less relative to the volume of the gas used. If the concentration of the oxidizing gas is below the above upper limit, oxidation of the mixture is suppressed, and a structure having desired characteristics is easily obtained. In addition, oxidative decomposition of the generated structure can be suppressed.
[0089] The supply rate (flow rate) of the inert gas is usually 200 mL / min or more, preferably 500 mL / min or more, more preferably 1000 mL / min or more, and usually 7000 mL / min or less, preferably 6000 mL / min or less, more preferably 5000 mL / min or less, relative to 1 g of the mixture.
[0090] The heat treatment temperature is preferably 150°C or higher, more preferably 200°C or higher, further preferably 240°C or higher (e.g. 250°C or higher and higher than 300°C), and is preferably 500°C or lower (e.g. lower than 500°C), more preferably 470°C or lower (e.g. 450°C or lower), and further preferably 420°C or lower (e.g. 400°C or lower and lower than 400°C). The heat treatment temperature is preferably 150°C or higher and 500°C or lower (e.g. higher than 300°C and lower than 500°C), more preferably 150°C or higher and 470°C or lower (e.g. higher than 300°C and lower than 470°C), further preferably 200°C or higher and 450°C or lower (e.g. higher than 300°C and lower than 450°C), and particularly preferably 240°C or higher and 420°C or lower (e.g. higher than 300°C and lower than 420°C).
[0091] The present inventors have found that the characteristic pore structure of porous carbon can be obtained by heat treating the mixture obtained by step (1) in an inert gas atmosphere at a temperature preferably above the lower limit and below the upper limit or within the above range. The reason is not clear, but the following non-limiting mechanism of action can be considered.
[0092] Through the above-mentioned heat treatment, in the mixture, the carbon source and the calcium compound compatible with the carbon source by hydrogen bonding are phase-separated starting from the detachment of crystal water from the mixture or the dehydration reaction of the carbon source. It can be further considered that the carbon source is solidified by the dehydration reaction of the carbon source, and the structure of the state in which the carbon source and the calcium compound are phase-separated is fixed. At this time, at least a part of the calcium compound that has undergone phase separation (preferably more than 50% by mass of the calcium compound that has undergone phase separation, more preferably almost all or all) is three-dimensionally continuously connected. In the subsequent carbonization process, the carbon source is insoluble in hot water or hot acid by being aromaticized (carbonized), and in the subsequent calcium compound removal process, the calcium compound is removed from the carbide (preferably by acid-based cleaning). It can be considered that: since the traces after the removal of the calcium compound become pores, the characteristic pore structure of porous carbon can be obtained by the phase separation of the calcium compound achieved by the above-mentioned heat treatment.
[0093] The heating rate in the heat treatment step is preferably 2°C / min or more, more preferably 5°C / min or more, and further preferably 10°C / min or more. If the heating rate is above the lower limit, it is easy to obtain the desired pore volume and / or the desired mass transfer coefficient. The upper limit of the heating rate is not particularly limited, but is preferably 200°C / min or less from the viewpoint of easily achieving uniform heat treatment.
[0094] The heat treatment time is appropriately selected according to the heat treatment temperature, the supply amount of the inert gas, etc. For example, it is more than 0.1 hour, preferably more than 0.2 hour, more preferably more than 0.3 hour, more preferably more than 0.5 hour, and preferably less than 24 hours, more preferably less than 12 hours, and more preferably less than 8 hours. If the heat treatment time is more than the aforementioned lower limit, it is easy to fully separate. If the heat treatment time is less than the aforementioned upper limit, it is a moderate time from the viewpoint of economy, so it is preferred.
[0095] As the device used in the heat treatment, various furnaces such as a converter, a fluidized bed furnace, a fixed layer furnace, a mobile layer furnace, and a mobile bed furnace can be used; and various dryers such as a spray dryer, a mobile dryer, a stirring dryer, a roller dryer, and a thin film evaporator can be used. In addition, a continuous furnace or a continuous dryer that continuously inputs the material for heat treatment and takes out the material after heat treatment, or an intermittent furnace or an intermittent dryer that discontinuously performs the above operation can be used. The heating means can be any means that can heat to a specified temperature, for example, it can be electric heating, gas combustion type heating, microwave heating, high-frequency induction heating, electric heating, etc. In addition, these heating means can be used alone or in combination.
[0096] <Step (3)>
[0097] In the step (3), the mixture phase-separated in the step (2) is heat-treated in an inert gas atmosphere to be carbonized.
[0098] The heat treatment temperature is preferably 500° C. or higher, more preferably more than 550° C., further preferably 600° C. or higher, particularly preferably 650° C. or higher, and preferably 1300° C. or lower, more preferably 1200° C. or lower, and further preferably 1000° C. or lower. When the heat treatment temperature is higher than the lower limit or higher than the lower limit and lower than the upper limit, the pore volume of the obtained porous carbon of 2 nm or more and 200 nm or less tends to be appropriate, and porous carbon having desired adsorption characteristics tends to be obtained. In addition, in the subsequent step of removing calcium compounds from carbides, there is a tendency for calcium compounds to be easily removed.
[0099] The heat treatment of the phase-separated mixture may be carried out in multiple stages. For example, the heat treatment may be carried out at 500 to 900° C., and thereafter, at 900 to 1300° C. From the viewpoint of easily obtaining a porous carbon having the desired adsorption characteristics, it is preferred not to carry out the heat treatment in multiple stages. However, it is not excluded to carry out the heat treatment in multiple stages.
[0100] The heating rate during the heat treatment step is preferably 2°C / min or more, more preferably 5°C / min or more, and further preferably 10°C / min or more. If the heating rate is above the lower limit, the desired pore volume can be easily obtained. The upper limit of the heating rate is not particularly limited, but is preferably 200°C / min or less from the viewpoint of easily achieving uniform heat treatment.
[0101] The heat treatment time is appropriately selected according to the heat treatment temperature, the supply amount of the inert gas, etc. For example, it is more than 0.5 hours, more preferably more than 0.7 hours, more preferably more than 0.8 hours, and preferably less than 24 hours, more preferably less than 12 hours, and more preferably less than 8 hours. If the heat treatment time is more than the aforementioned lower limit, it is easy to fully carbonize. If the heat treatment time is less than the aforementioned upper limit, it is an appropriate time from the viewpoint of economy, so it is preferred. The above-mentioned heat treatment time when heat treatment is implemented in multiple stages refers to the total heat treatment time.
[0102] The inert gas, its supply amount, and the furnace used for the heat treatment can be the same as those in step (2).
[0103] <Step (4)>
[0104] In step (4), the calcium compound is removed from the obtained carbide, thereby obtaining porous carbon.
[0105] The removal of calcium compounds is preferably carried out by acid cleaning. Examples of the acid used in acid cleaning include hydrochloric acid, sulfuric acid, nitric acid, and the like. From the viewpoint that metal compounds in carbides are easily dissolved, impurities such as sulfur are not easily left, and oxidation of carbides is easily inhibited, hydrochloric acid is preferably used. The acid concentration during acid cleaning can be appropriately changed according to the type of acid used. For example, when hydrochloric acid is used, the concentration of hydrochloric acid is preferably 0.01 to 1.0 mol / L, and more preferably 0.05 to 0.5 mol / L. If the concentration of hydrochloric acid is within the above range, metal compounds are easily removed and hydrochloric acid is not easily left in carbides, so it is preferred.
[0106] The pH of the acid during acid cleaning can be appropriately changed according to the type, concentration, temperature, etc. of the acid used. The pH of the acid is preferably 3 or less, more preferably 2.5 or less. If the pH of the acid is below the above upper limit, the metal compound can be easily and efficiently removed.
[0107] Acid cleaning can be performed, for example, by immersing the obtained carbide in the aforementioned acid. In the case of acid cleaning by immersion in an acid, the mass ratio of the acid to the carbide can be appropriately adjusted according to the type, concentration and temperature of the acid used. The mass of the carbide to be impregnated is preferably 2% by mass or more, more preferably 5% by mass or more, and preferably 50% by mass or less, more preferably 30% by mass or less, relative to the mass of the acid. If the mass ratio of the carbide to be impregnated to the mass of the acid is above the aforementioned lower limit and below the aforementioned upper limit, a sufficient cleaning effect is easily obtained.
[0108] The method of impregnating the carbide in the acid is not particularly limited. It may be a method of continuously adding the acid and retaining it for a predetermined time, and then taking it out while impregnating it, or a method of impregnating the carbide in the acid and retaining it for a predetermined time, adding the acid again after dehydration, and repeatedly impregnating and dehydrating it. In addition, it may be a method of renewing all the acid, or a method of renewing a part of the acid. In addition, the acid may be stirred during the impregnation.
[0109] The atmosphere for acid cleaning is not particularly limited and can be appropriately selected according to the cleaning method used. Acid cleaning is usually performed in an air atmosphere.
[0110] The time for immersing the carbide in the acid can be appropriately adjusted according to the acid used, the treatment temperature, etc. From the viewpoint of easy and sufficient removal of the metal compound, it is preferably 5 minutes or more, and from the viewpoint of productivity, it is preferably 60 minutes or less, more preferably 40 minutes or less, and further preferably 35 minutes or less.
[0111] Preferably, after the carbide is acid-cleaned, the acid in the porous carbon is removed by water washing. The acid cleaning and water washing can be repeated until the calcium compound in the porous carbon can be removed to a desired extent. In addition, from the viewpoint of the removal efficiency of the calcium compound and the residual acid, the solution temperature during the acid cleaning and water washing is preferably higher, usually above 60°C.
[0112] As one embodiment of the present invention, when the heat treatment of the phase-separated mixture is performed in multiple stages, acid cleaning can be performed between the multiple stages of heat treatment. For example, after the phase-separated mixture is heat-treated in step (2) (for example, at 500 to 900° C.), acid cleaning can be performed, and then heat-treated (for example, at 900 to 1300° C.).
[0113] The porous carbon after acid cleaning and water washing can be dried using a known dryer such as a hot air dryer or a reduced pressure dryer. Drying is preferably performed at a temperature of 50 to 150° C. If the drying temperature is within the above range, oxidation of the porous carbon is less likely to occur and drying is performed appropriately, which is preferred.
[0114] The dried porous carbon can be crushed. By crushing, the shape and particle size of the porous carbon finally obtained can be controlled to a desired shape and particle size. The crushing method is not particularly limited. For example, a ball mill, a centrifugal roller mill, a ring roller mill, a centrifugal ball mill, a jet mill, a cone crusher, a double roll crusher, a disc crusher, a rotary crusher and other known crushers can be used alone or in combination.
[0115] In the method for manufacturing porous carbon, a classification process may be further included after the pulverization process. For example, by removing particles that are extremely small or large compared to the desired particle size, porous carbon with a narrow particle size distribution range can be obtained. The classification method is not particularly limited. As examples of classification methods, classification using a sieve, wet classification, and dry classification can be listed. As a wet classifier, for example, a classifier using the principles of gravity classification, inertial classification, hydraulic classification, centrifugal classification, etc. can be listed. As a dry classifier, a classifier using the principles of sedimentation classification, mechanical classification, centrifugal classification, etc. can be listed. From the viewpoint of economy, a dry classifier is preferably used.
[0116] In order to prevent the surface from being oxidized during pulverization, the pulverization step and the classification step are preferably performed in an inert gas atmosphere.
[0117] Crushing and classification can also be performed using one device. For example, a jet mill with a dry classification function can be used to perform crushing and classification. Furthermore, a device in which a crusher and a classifier are independent can also be used. In this case, crushing and classification can also be performed continuously or discontinuously.
[0118] The porous carbon of the present invention has a characteristic pore structure, and therefore, the present invention also targets porous carbon as an adsorbent.
[0119] By having this characteristic pore structure, the porous carbon can show excellent adsorption characteristics for molecules or viruses with a relatively large diameter (e.g., 2 to 200 nm). Therefore, the present invention also targets porous carbon as an adsorbent for adsorbing proteins or porous carbon as an adsorbent for adsorbing viruses.
[0120] In a preferred embodiment, when the porous carbon is allowed to adsorb albumin for 5 minutes, the adsorption rate is preferably 50% or more, more preferably 60% or more, and particularly preferably 70% or more.
[0121] In another preferred embodiment, when the porous carbon is allowed to adsorb albumin for 60 minutes, the adsorption rate is preferably 60% or more, more preferably 70% or more, and particularly preferably 90% or more.
[0122] In addition, in a preferred embodiment, the ratio (%) of the adsorption rate of albumin after 5 minutes of adsorption to the adsorption rate of albumin after 60 minutes of adsorption [(adsorption rate after 5 minutes of adsorption / adsorption rate after 60 minutes of adsorption)×100] is preferably 60% or more, more preferably 70% or more, and particularly preferably 80% or more.
[0123] In a preferred embodiment, when the porous carbon is allowed to adsorb antibodies (e.g., γ-globulin derived from human plasma or γ-globulin derived from bovine plasma) for 5 minutes, the adsorption rate is preferably 30% or more, more preferably 50% or more, and particularly preferably 60% or more.
[0124] In another preferred embodiment, when the porous carbon is allowed to adsorb the antibody for 60 minutes, the adsorption rate is preferably 50% or more, more preferably 60% or more, and particularly preferably 70% or more.
[0125] In addition, in a preferred embodiment, the ratio (%) of the adsorption rate after 5 minutes of adsorption of the antibody to the adsorption rate after 60 minutes of adsorption of the antibody [(adsorption rate after 5 minutes of adsorption / adsorption rate after 60 minutes of adsorption) × 100] is preferably 60% or more, more preferably 70% or more, and particularly preferably 80% or more.
[0126] In a preferred embodiment, if it is made to adsorb viruses (such as feline calicivirus), the porous carbon has a preferred thickness of 10 3.0 TCID 50 / mL or less, more preferably 10 2.5 TCID 50 / mL or less, particularly preferably 10 1.5 TCID 50 / mL or less antiviral properties.
[0127] The above-mentioned adsorption rate of albumin or antibody on porous carbon and antiviral properties can be measured by the method described in the examples described later.
[0128] Example
[0129] Hereinafter, the present invention will be specifically described with reference to Examples, but these Examples are not intended to limit the scope of the present invention.
[0130] [Analysis method]
[0131] <Mass transfer coefficient based on nitrogen adsorption method>
[0132] The porous carbon as the measurement sample is filled into the test tube. The test tube is placed in the "Autosorb-iQ-MP" manufactured by Quantachrome, and the pressure is temporarily reduced while cooling to -196°C. Thereafter, nitrogen gas (purity 99.999%) is adsorbed onto the measurement sample at a specified relative pressure. The amount of nitrogen adsorbed onto the sample when the equilibrium pressure is reached at each specified relative pressure is measured, and an adsorption isotherm is prepared.
[0133] The mass transfer coefficient was obtained by analyzing the data of the prepared nitrogen adsorption isotherm. Specifically, the pressure change of nitrogen until the adsorption equilibrium is reached at each specified relative pressure was converted into the mass transfer coefficient using the LDF approximation. At this time, the relative pressure was 1.0×10 -4 Above and 1.0×10 -3 The conversion into the mass transfer coefficient was performed so that the number of plots in the following range became at least 5.
[0134] Make the relative pressure (P / P 0 ) as the x-axis and the mass transfer coefficient as the y-axis. -4 Above and 1.0×10 -3 Draw an approximate straight line within the following range and find its slope (a) and relative pressure 1.0×10 -3 The value of the mass transfer coefficient when (b).
[0135] <Volume and Mode Diameter of Pores of 2 nm or More and 200 nm or Less by Nitrogen Adsorption Method>
[0136] The nitrogen adsorption isotherm obtained as described above is analyzed by the BJH method to calculate the volume of pores having a pore diameter of 2 nm or more and 200 nm or less.
[0137] In addition, the nitrogen adsorption isotherm obtained as described above was analyzed by the BJH method, and the logarithmic differential pore volume distribution (dV / d(logD)) obtained by differentiating the cumulative pore volume (V) using the common logarithm of the pore diameter (D) was obtained, and the pore diameter with the largest appearance ratio was used as the mode diameter of the measured sample.
[0138] <Specific surface area>
[0139] The nitrogen adsorption isotherm obtained as described above was analyzed by a multipoint method using the BET formula, and the specific surface area of the measurement sample was calculated from an approximate straight line in the range of relative pressure of 0.05 to 0.1 of the obtained curve.
[0140] <Volume Density>
[0141] The bulk density of the measurement sample was measured using a powder tester PT-X manufactured by Hosokawa Micron Co., Ltd. Specifically, the measurement sample was placed in an automatic tap density measuring unit, and the bulk density was calculated from the volume after tapping 3,000 times.
[0142] <Average primary particle size>
[0143] The sample was placed in an aqueous solution containing 5% by mass of a surfactant ("Toriton X100" sold by Wako Pure Chemical Industries, Ltd.), and treated with an ultrasonic cleaner for more than 10 minutes to disperse it in the aqueous solution. The particle size distribution was measured using a particle size / particle size distribution measuring device ("MICROTRAC MT3300EXII" manufactured by MICROTRAC BEL) using the dispersion. The particle size at which the cumulative volume was 50% was set as the average primary particle size of the porous carbon as the sample.
[0144] <Adsorption characteristics of albumin and antibodies>
[0145] Prepare a 2g / L aqueous solution of albumin and a 1g / L aqueous solution of an antibody (γ-globulin from human plasma). Into two containers, introduce 25mL of the prepared albumin aqueous solution and 0.1g of porous carbon, and into another two containers, introduce 25mL of the prepared antibody aqueous solution and 0.1g of porous carbon. Oscillate one container containing the albumin aqueous solution and one container containing the antibody aqueous solution at 25±2°C for 5 minutes to allow the albumin or antibody to adsorb to the porous carbon, and oscillate another container containing the albumin aqueous solution and another container containing the antibody aqueous solution at 25±2°C for 60 minutes to allow the albumin or antibody to adsorb to the porous carbon. After oscillation, use a membrane filter to remove the porous carbon from each solution. Next, the absorbance of each filtrate is measured by UV visible absorbance measurement to determine the molar concentration of each aqueous solution. According to the molar concentration C determined 1 and the molar concentration C of each aqueous solution before mixing with the porous carbon 2 , the adsorption rate (%) was calculated by the following formula.
[0146] Adsorption rate = [(C 2 -C 1 ) / C 2 ]×100
[0147] In addition, for each aqueous solution, the ratio (%) of the adsorption rate after 5 minutes of adsorption to the adsorption rate after 60 minutes of adsorption [(adsorption rate after 5 minutes of adsorption / adsorption rate after 60 minutes of adsorption)×100] was determined.
[0148] <Anti-Viral Properties>
[0149] The infectivity value of feline calicivirus was determined by the TCID50 method.
[0150] Specifically, after 10 mg of porous carbon was introduced into a test tube, the mixture was adjusted to 10 5.1 TCID 50 / mL virus solution 10mL. Oscillating mixing was performed at 150 rpm for 10 minutes at room temperature as the hypersensitivity time. After the hypersensitivity time, the filtrate was filtered using a 0.45μm membrane filter. Next, the filtrate was diluted 10 times in stages using cell maintenance medium, and each dilution was inoculated into the cultured cells of a 96-well microplate and incubated at 5% CO 2 The cells were cultured at 37° C. for 5 days in the presence of gas. The cultured cells were observed under a microscope, and the presence or absence of virus proliferation was confirmed by the appearance of CPE (cell modification) in the cultured cells, and the virus concentration was calculated.
[0151] [Example 1]
[0152] Mix 1 g of glucose (sold by Fujifilm Wako Pure Chemical Industries, Ltd.), 2 g of calcium chloride dihydrate (200 parts by mass relative to 100 parts by mass of glucose), and 1 g of ion exchange water (100 parts by mass relative to 100 parts by mass of glucose). The resulting mixture is heated to 200°C at a heating rate of 10°C / min under a nitrogen gas flow of 1250 mL / min relative to 1 g of the mixture, and heat treated (phase separated) at this temperature for 30 minutes. Next, while circulating nitrogen at the same gas supply rate, heat to 700°C at a heating rate of 10°C / min, and heat treated (carbonized) at this temperature for 60 minutes to obtain a carbide. The carbide is immersed in 0.1 mol / L hydrochloric acid, stirred at 80°C for 30 minutes, washed, and then taken out onto a Buchner funnel. Wash with water until the pH of the filtrate is in the range of 6 to 8. After acid washing and water washing are repeated 3 times, hot air drying is performed at 80°C.
[0153] [Example 2]
[0154] Porous carbon was obtained in the same manner as in Example 1 except that the phase separation temperature was changed from 200°C to 250°C.
[0155] [Example 3]
[0156] Porous carbon was obtained in the same manner as in Example 1 except that the phase separation temperature was changed from 200°C to 350°C.
[0157] [Example 4]
[0158] A porous carbon was obtained in the same manner as in Example 3 except that the amount of calcium chloride dihydrate added was changed from 200 parts by mass to 300 parts by mass relative to 100 parts by mass of glucose.
[0159] [Example 5]
[0160] Porous carbon was obtained in the same manner as in Example 3 except that the temperature increase rate for phase separation was changed from 10° C. / min to 5° C. / min.
[0161] [Example 6]
[0162] Porous carbon was obtained in the same manner as in Example 3 except that the temperature increase rate for phase separation was changed from 10° C. / min to 20° C. / min.
[0163] [Example 7]
[0164] Porous carbon was obtained in the same manner as in Example 3 except that starch (derived from corn, with an amylose content of about 26%, sold by Fujifilm and Wako Pure Chemical Industries, Ltd.) was used instead of glucose.
[0165] [Example 8]
[0166] A porous carbon was obtained in the same manner as in Example 7 except that the amount of calcium chloride dihydrate added was changed from 200 parts by mass to 300 parts by mass based on 100 parts by mass of starch.
[0167] [Comparative Example 1]
[0168] Porous carbon was obtained in the same manner as in Example 1 except that the phase separation step was not performed.
[0169] [Comparative Example 2]
[0170] A porous carbon was obtained in the same manner as in Example 1 except that the temperature for heat treatment (phase separation) of the mixture of glucose, calcium chloride dihydrate and ion-exchanged water was changed from 200°C to 140°C.
[0171] [Comparative Example 3]
[0172] Mix 1 g of polyvinyl alcohol (PVA) with 1 g of magnesium oxide particles having an average particle size of 10 nm (100 parts by mass relative to 100 parts by mass of PVA). Heat the resulting mixture to 700°C at a heating rate of 10°C / min under a nitrogen gas flow of 1250 mL / min relative to 1 g of the mixture, and heat treat (carbonize) at this temperature for 60 minutes to obtain a carbide. Immerse the carbide in 1 mol / L sulfuric acid, stir at 80°C for 30 minutes, wash it, and then take it out onto a Buchner funnel. Wash with water until the pH of the filtrate reaches the range of 6 to 8. Repeat the acid washing and water washing 3 times, and then dry it with hot air at 80°C.
[0173] [Comparative Example 4]
[0174] As the activated carbon, CARBORAFFIN manufactured by Osaka Gas Chemical Co., Ltd. was used.
[0175] The production conditions of the porous carbon obtained in Examples and Comparative Examples are shown in Table 1, and the physical properties are shown in Table 2. The porous carbon obtained in Examples 1 to 8 and Comparative Examples 1 to 4 was in a granular form.
[0176] [Table 1]
[0177] Table 1: Fabrication conditions of porous carbon
[0178]
[0179] [Table 2]
[0180] Table 2: Physical properties of porous carbon
[0181]
[0182] It is known that the porous carbons of Examples 1 to 8 can exhibit high adsorption properties for albumin, antibodies, and feline calicivirus even when the adsorption time is short. On the other hand, the porous carbons of Comparative Examples 1 to 4 have insufficient adsorption properties for albumin, antibodies, and feline calicivirus.
[0183] Industrial Applicability
[0184] The porous carbon of the present invention has a high adsorption property for molecules or viruses having a relatively large diameter (eg, 2 to 200 nm), and therefore can be suitably used as an adsorbent material for adsorbing such molecules.
Claims
1. Porous carbon, wherein: The pressure change of nitrogen gas until adsorption equilibrium is reached at each specified relative pressure in the measurement of nitrogen adsorption isotherm is converted into the mass transfer coefficient by using LDF approximation, and the relative pressure is 1.0×10 -4 Above and 1.0×10 -3 The slope of the approximate straight line obtained by linearly approximating the relationship between the relative pressure and the mass transfer coefficient when the following is 4 or more, The pore volume of pores with a diameter of 2 nm or more and 200 nm or less calculated by the BJH method based on the nitrogen adsorption isotherm is 0.8 cm 3 / g or above.
2. The porous carbon according to claim 1, wherein In the approximate straight line, the relative pressure is 1.0×10 -3 The mass transfer coefficient is 3.0×10 -3 above.
3. The porous carbon according to claim 1 or 2, wherein the volume density is less than 0.10 g / cm 3 .
4. The method for producing porous carbon according to claim 1 or 2, comprising: (1) A step of obtaining a mixture containing a carbon source and a calcium compound; (2) a step of heat-treating the mixture in an inert gas atmosphere to phase separate the carbon source and the calcium compound; (3) a step of heat treating the phase-separated mixture in an inert gas atmosphere to obtain a carbide; and (4) A step of removing calcium compounds from the carbide.
5. The method according to claim 4, wherein: The temperature in the phase separation step of the step (2) is 150° C. or higher and 500° C. or lower. The porous carbon according to claim 1 or 2, which is an adsorbent material. The porous carbon according to claim 1 or 2, which is an adsorption material for adsorbing proteins. The porous carbon according to claim 1 or 2, which is an adsorption material for adsorbing viruses.
Citation Information
Patent Citations
Porous carbon material, adsorbent, filler, mask, adsorbing sheet, and carrier
JP2011042569A
Adsorbent, carbon / polymer composite and adsorptive sheet adsorbing virus and / or bacterium
JP2012187571A
Porous carbon
JP2016041656A
Adsorbent for protein purification
JP2018001057A
Determining a target cell for handover between neighboring cells based on measurement reports and cell identifiers
JP2022119926A